Comprensión lectora en niños con síndrome de Asperger y niños sin síndrome de Asperger - Guimet Reátegui, Sofía Alejandra (2015)
The following study is a comparative type, since it seeks to identify the differences in reading comprehension between a group of normal children and children with Asperger syndrome. To do this, we evaluated 8 children with Asperger syndrome and 8 regular children, both groups between 7 and 12 years. Data were taken into account such as age and grade. And in the case of children with Asperger syndrome, was also taken into consideration the attendance at therapy, frequency of attendance and age of diagnosis of the syndrome. Regarding the reading comprehension variable, we used the Peruvian adaptation Assessment Battery Readers Processes PROLEC-R (2007). Results indicated no significant differences between groups. With this we can show that the group of children with Asperger's Syndrome have not really significant cognitive difficulties and they can understand texts like a regular kid.